Pharmacological Inhibition of Galectin-3 Ameliorates Diabetes-Associated Cognitive Impairment, Oxidative Stress and Neuroinflammation in vivo and in vitro - Yin Q; Chen J; Ma S; Dong C; Zhang Y; Hou X; Li S; Liu B (Dove Medical Press, 2020)
Qingqing Yin,1– 3 Jian Chen,1 Shizhan Ma,4 Chuanfang Dong,5 Yue Zhang,2,3 Xunyao Hou,1 Shangbin Li,1,3 Bin Liu6,7 1Department of Geriatric Neurology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong 250021, People’s Republic of China; 2School of Medicine, Shandong University, Jinan 250021, People’s Republic of China; 3Department of Geriatrics, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong 250021, People’s Republic of China; 4Department of Endocrinology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong 250021, People’s Republic of China; 5Department of Geriatrics, Jinan Hospital, Jinan, Shandong 250013, People’s Republic of China; 6Department of Neurology, The First Affiliated Hospital of Shandong First Medical University, Jinan 250014, People’s Republic of China; 7Department of Neurology, Shandong Provincial Qianfoshan Hospital, Shandong University, Jinan 250014, People’s Republic of ChinaCorrespondence: Shangbin LiDepartment of Geriatrics, Department of Geriatric Neurology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong 250021, People’s Republic of ChinaTel +86-15168889891Email lishangbin@126.comBin LiuDepartment of Neurology, The First Affiliated Hospital of Shandong First Medical University, Jinan, 250014, China, Department of Neurology, Shandong Provincial Qianfoshan Hospital, Shandong University, Jinan 250014, People’s Republic of ChinaTel +86-15098740686Email lbliubinlb@163.comBackground: In diabetes, cognitive impairment is linked with oxidative stress and neuroinflammation. As the only chimeric member of the galectin family, galectin-3 (Gal3) induces neuroinflammation and cognitive impairment in models of Alzheimer’s disease (AD); however, its role in diabetes-associated cognitive impairment is not established.Methodology: Here, we investigated the effects of Gal3 inhibition on cognitive impairment and the possible underlying molecular events in diabetes. We investigated the effects of the Gal3 inhibitor modified citrus pectin (MCP; 100 mg/kg/day oral for 6 weeks) in vivo in high-fat diet (HFD)/streptozotocin (STZ)-induced diabetic rats. Additionally, the effects of MCP on high glucose (HG)-stimulated BV-2 microglial cells were investigated in vitro.Results: We found that MCP attenuated memory impairment in diabetic rats in the Morris water maze test and reduced insulin resistance, oxidative stress, and neuroinflammation. In HG-stimulated BV-2 microglial cells, MCP increased cell viability and decreased oxidative stress and the production of proinflammatory cytokines.Conclusion: The results of this study indicate that the inhibition of Gal3 by MCP ameliorates diabetes-associated cognitive impairment, oxidative stress, and neuroinflammation, suggesting that Gal3 could be a potential new target for therapeutic intervention to prevent cognitive impairment in diabetes.Keywords: galectin-3, oxidative stress, neuroinflammation, cognitive impairment, diabetes